Using Combinatorial Inkjet Printing for Synthesis and Deposition of Metal Halide Perovskites in Wavelength‐Selective Photodetectors. Issue 4 (2nd December 2021) - Schröder, Vincent R. F.; Hermerschmidt, Felix; Helper, Sabrina; Rehermann, Carolin; Ligorio, Giovanni; Näsström, Hampus; Unger, Eva L.; List-Kratochvil, Emil J. W.
Abstract : Metal halide perovskites have received great attention in recent years, predominantly due to the high performance of perovskite solar cells. The versatility of the material, which allows the tunability of the bandgap, has led to its use in light‐emitting diodes, photo, and X‐ray detectors, among other optoelectronic device applications. Specifically in photodetectors, the tunability of the bandgap allows fabrication of spectrally selective devices. Utilizing a combinatorial inkjet printing approach, multiple perovskite compositions absorbing at specific wavelengths in a single printing step are fabricated. The drop‐on‐demand capabilities of inkjet printing enable the deposition of inks in a precise ratio to produce specific perovskite compositions in the printed thin film. By controlling the halide ratio in the compositions, a mixed halide gradient ranging from pure MAPbI3 via MAPbBr3 to MAPbCl3 is produced. The tunability in the absorption onset from 410 to 790 nm is demonstrated, covering the whole visible spectrum, with a precision of 8 nm steps for MAPb(Br x Cl1− x )3 compositions. From this range of mixed halide perovskites, photodetectors which show spectral selectivity corresponding to the measured absorption onset are demonstrated, paving the way for use in a printed visible light spectrometer without the need for a dispersion element. Abstract : The tunable bandgap of metal halide perovskites can be exploited for the fabrication of wavelength‐selective photodetectors. Combinatorial inkjet printing to fabricate multiple phase‐pure perovskite compositions in a single printing step is used, with absorption onsets covering the entire visible spectral range. When implemented in photodetectors, their spectral selectivity paves the way for use in a visible light spectrometer.